PENDAMPINGAN PEMASARAN PRODUK ABON LELE HASIL HOME INDUSTRY BERBASIS MEDIA SOSIAL FACEBOOK PADA UMKM POKLASAR ERWINA PAGELARAN PEKON PAGELARAN (LP3K Lampung, 2021)
There are many promotional media that can be used, ranging from the general to the unique or new, until now they are used as promotional media, which have turned out to be quite effective in getting new potential customers. The aim is to implement a social media strategy that can be implemented by businesses to expand their marketing area. The object of this Community Service activity is processed catfish shredded products. This activity produces a social media strategy that can be implemented at Poklasar Erwina Pagelaran so that it can expand the marketing area. With the social media strategy that has been formulated, it is hoped that business actors will get an idea of what needs to be prepared in using social media and how to use social media.